Patterns and locations of sprouts on intact tubers of a multiple sprouting Dioscorea rotundata poir. variety, Pepa - Aighewi, B.A.; Asiedu, Robert; Akoroda, M.O. (2002)
Tuber of most varieties of white Guinea yam, Dioscorea rotundata Poir., produce a single sprout in the proximal region after the break dormancy. The location and pattern of sprout formation on intact tubers of a multiple sprouting variety, Pepa were studied. Only 0.4% of the tubers had a single sprouts at the proximal apex of the tuber, while 85.5 produced a bunch of sprouts in that region up to 96.1% of tubers had sprouts only in the proximal region, while a small proportion had sprouts all over the tuber (1.2%), only in the middle portion (0.3%), or only in the distal (tail) portion (0.8%).